Prevalence of anemia in adolescent girls and its association with certain demographic variables: our experience from rural Telangana - Reshmi, Panchasheela S.; Takalkar, Anant Arunrao (International Journal Of Community Medicine And Public Health, 2020)
Background: Adolescents constitute over 21.4% of the population in India and adolescent girls constitute about 10 percent of the Indian population. This age group needs special attention because of the turmoil of adolescence which they face due to the different stages of development that they undergo, different circumstances that they come across, their different needs and diverse problems. The objectives of the study were to determine the prevalence of anaemia in the study population and to assess the socio-demographic risk factors associated with the anaemia. Methods: Community based cross sectional study conducted in adolescent girls aged 10 to 19 years, permanently residing in the rural field practice area of Department of Community Medicine, Kamineni Institute of Medical Sciences, Narketpally during September 2010 to September 2012. Results: Majority of families belong to upper lower socio-economic status (57.7%) according to BG Prasad’s classification. Age-wise prevalence of anaemia shows that prevalence of anaemia was highest (69%) in 18 to 19 years age group and least (37.5%) in the age group of 16 to 17 years. Majority of subjects with anaemia were having mild anaemia (80.2%) followed by moderate anaemia (19.2%) and severe anaemia (0.6%) respectively. Highest prevalence (68.1%) was found in joint or extended and least prevalence (56.1%) was found in nuclear families. Highest prevalence (75.0%) in subjects belonging to large family and least (54.5%) with small family. Conclusions: Prevalence of anaemia was 59% with majority of study subjects having mild to moderate anaemia. Prevalence of anaemia in these girls had a significant association with socioeconomic status of the family.